THEMES OF FAMILY LOYALTY AND NATIONAL BETRAYAL IN AMERICAN LITERATURE (Bulletin of Innovative Research, 2026)
This article discusses the issue of loyalty and betrayal in humans, the fact that these events motivate people to live and hurt hearts, and the universal loyalty of the novel, which is the essence of the work. It is said that the writer managed to reveal the spiritual development of the nation through the qualities of courage, fortitude, humanity and patience, loyalty, betrayal.